Protective Effects of Methanolic Fruit Extract of Solena amplexicaulis in Carbon Tetrachloride Induced Hepatotoxicity on Rat (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Carbon tetrachloride; Silymarin; Solena amplexicaulis; hepatoprotective activity; biochemical parameterDOI: http://dx.doi.org/10.3329/sjps.v3i2.5953 S.J. Pharm. Sci 3(2): 01-06